Deprivation of citizenship, undocumented labor and human trafficking: Myanmar migrant workers in Thailand - Steve Kwok Leung Chan (2018)
© Regions & Cohesion. Thailand is a popular destination for irregular labor migration from Myanmar. Among some three million Burmese migrant workers in Thailand, more than half are undocumented. Undocumented migrant workers rely on brokers to smuggle them into Thailand. Some undocumented migrant workers are lured, tricked, and forced to work but they are not rewarded with a reasonable wage. A conceptual framework of the shadow sector of labor migration is formulated in this study, which attempts to explain why ethnic minorities in Myanmar are socially categorized by the level of their deprived citizenship. Those low in the hierarchy of categorization are likely to fall into the shadow sector of the labor migration process. Ethnic minorities from areas of insurgency are exposed to a high risk of human trafficking.